PENGARUH SENAM NIFAS TERHADAP PROSES INVOLUSI UTERI PADA IBU POST PARTUM DI RSUD DR.SOEROTO NGAWI - Frilasari, Heni; LadismaKyki, (JURNAL KEPERAWATAN SEHAT, 2014)
Puerperium is a process of health recovery in the puerperium is a very importance to mothers after childbirth and postpartum mothers in general are afraid of making a lot of movement and mothers are usually concerned the movements made will cause undesirable effects. This research uses design experiment between 2 pre-pasca test observations in one group (one group pre-post test desaign). Its population is the entire post-partum mothers in Hospital Dr. Soeroto Ngawi. Amount samples of 15 puerperal mothers, sampling technique is a non probability sampling type Consecutive sampling. Independent variable is puerperal gymnastic, the dependent variable is a uterine involution. Data obtained by using gymnastics guidelines and observations to determine the movement inpuerperal gymnastics and use the fingers of researchers, the observation data collection sheet to determine the uterine involution (High uterine fundus). The results of this research indicate a significant effect using the rank test to test with significance level of α = 0.05 results obtained α = 0.001. These results indicate, there is the effect puerperal gymnastics of process uterine involution atmothers post partum in Hospital Dr. SOEROTO Ngawi. This is caused by factors that affect uterine involution (early mobilization, nutritional status, breastfeeding, age, parity, puerperal and gymnastics). Expected mean doing gymnastics puerperal uterine involution may affect getting better, and vice versa then the role of the midwife is very required to always improve wishes puerperal mothers to do gymnastics puerperal with one of them gives an understanding of the importance of puerperal gymnastics for uterine involution process.Keyword:puerperalgymnastics,uterineinvolution